ENVIRONMENTAL POLICIES AND THEIR IMPACT ON MENTAL HEALTH: AN INTEGRATIVE LITERATURE REVIEW - Silva, Lívia Vieira Essado; Marques, Yasmine Fernandes; Guedes, Rafaella Yokota; Romano, Bruno Silva; Carvalho, Karla Cristina Naves de (CIPEEX, 2025)
The Unified Health System defines health as a complete state of physical, mental, and social well-being, and not merely the absence of disease. Thus, the importance of mental health care is evident, particularly when considering factors that directly influence it, such as environmental factors. This study aims to analyze the impact of environmental policies on mental health. It is an integrative literature review, which examined studies published in the last five years across major databases. The analysis revealed that the reduction of urban noise and contact with green spaces have a direct impact on the decrease of mental disorders such as depression, anxiety, and stress, leading to the conclusion that encouraging environmental policies is crucial for the preservation of mental health.